PERAN DASAWISMA DALAM PENGEMBANGAN DESA WISATA CAU BLAYU MARGA TABANAN - D.G.P. Yustiawan; P.D.Y. Utami; I.D.A.D. Mayasari; I.P.R.A. Putra (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Dasawisma is part of the Village PKK and has an important role within the Village scope. Cau Belayu Village itself has problems in terms of mobilizing the PKK in this case the Dasawisma field, the problem faced is the lack of understanding of Dasawisma members regarding their position and function in supporting the establishment of a tourism village. PKK consists of several cadres who have their respective duties and functions. The function of dasawisma is to supervise or cover 10-20 families around the neighborhood, the aim is to make it easier to provide and distribute information and be responsive if there are problems in the dasawisma group by submitting reports to the village/kelurahan. The method used in this activity is counseling and socialization in depth and directly to the village government. The legal basis for the formation of the PKK is Permendagri No. 1/2013 Concerning Community Empowerment Through the PKK Movement. This was further strengthened by the issuance of Presidential Decree No. 99/2017 concerning the PKK Movement, which is the driving force for the form of each PKK activity. With regulations that already contain the role and function of the PKK for the Village, in general in supporting and supporting the establishment of a Tourism Village, the PKK can have a positive effect on the realization of a Tourism Village which will later provide positive value to support the improvement of the village economy, especially in Cau Blayu Village. Marga subdistrict, Tabanan regency. Keywords: Dasawisma, Cau Belayu Tourism Village, Community Strengthening